1997
DOI: 10.12968/bjtr.1997.4.7.14414
|View full text |Cite
|
Sign up to set email alerts
|

Forensic occupational therapy: is it a developing specialism?

Abstract: Occupational therapists work in various specialisms within the field of mental health. Forensic psychiatry is one which is rapidly developing. Any occupational therapist wishing to work in this specialism would probably wish to know what they were ‘in for’. Media images of mentally ill criminals have shaped public attitudes and have hidden the realities about how interesting forensic psychiatric work can be.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…However, some does exist. Chacksfield (1997) traced the development of this distinct area of specialization and claimed that it ran in conjunction with the development of the Regional Secure Unit programme beginning around the early 1980s. However, it would appear that occupational therapy in these settings was poorly funded and therefore slower to develop as a priority.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…However, some does exist. Chacksfield (1997) traced the development of this distinct area of specialization and claimed that it ran in conjunction with the development of the Regional Secure Unit programme beginning around the early 1980s. However, it would appear that occupational therapy in these settings was poorly funded and therefore slower to develop as a priority.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…The majority of research regarding occupational therapy and criminal justice focuses on the context within institutional settings such as federal prisons and forensic units (Baker & McKay, 2001; Canadian Association of Occupational Therapists [CAOT], n.d.; Chacksfield, 1997;Crist et al, 2005;Eggers, Munoz, Sciulli, & Crist, 2006;Molineux & Whiteford, 1999;Whiteford, 1997), leading to a need for research and practice that extends beyond institutions to the community (DeVos, Hauser, Kitchen, & Ring, 2012;Dieleman & Steggles, 2013). A literature review by Clarke, de Visser, Martin, & Sadlo (2016) showed that research aiming to establish competencies for emerging occupational therapy practice settings remains "predominantly opinion-based" (p. 17) or focuses on identifying settings, services, and rationale for emerging practice (Clarke, 2012; Clarke, Martin, de Visser, & Sadlo, 2015; Holmes & Scaffa, 2009a).…”
Section: Occupational Therapy Emerging Practice and Criminal Justicementioning
confidence: 99%
“…Although descriptions of forensic occupational therapy roles and unique practice environments have been in the literature since the 1980s (Chacksfield, ), research evidence has remained marginal (College of Occupational Therapists, COT, 2012; O'Connell and Farnworth, ) and intervention studies are limited (e.g. Cullen et al ., ; MacKain and Streveler, ).…”
Section: Introductionmentioning
confidence: 99%